2019
DOI: 10.1155/2019/4676354
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Sealers Modified with Silver Vanadate: Antibacterial, Compositional, and Setting Time Evaluation

Abstract: The incorporation of nanoparticles into endodontic sealers aims at increasing antimicrobial activity of the original material. Aim. The aim of this study is to incorporate the nanostructured silver vanadate decorated with silver nanoparticles (AgVO3, at 2.5%, 5%, and 10%) into three endodontic sealers and evaluate the antibacterial activity of freshly sealers, surface topography and chemical composition, and setting time. Material and Methods. The AgVO3 was incorporated into AH Plus, Sealer 26, and Endomethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Teixeira et al., 2019 [ 20 ] found that after modifying sealer, Endomethasone N and AH-Plus endodontic cement with the addition of 2.5, 5 and 10% β-AgVO 3 , there was better inhibition for the groups of 5 and 10% for Sealer, 2.5, 5 and 10% for Endomethasone, while AH-Plus presented similar results to the control group. In another study by Teixeira et al., 2019 [ 12 ] in which he added the same proportions to the same materials previously mentioned, there was complete inhibition of the growth of E. Faecalis, however, without significant differences between the groups, including control. In another study by Teixeira et al., 2017 [ 19 ], the incorporation of β-AgVO 3 did not increase the antimicrobial activity of AH Plus against E. Faecalis.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Teixeira et al., 2019 [ 20 ] found that after modifying sealer, Endomethasone N and AH-Plus endodontic cement with the addition of 2.5, 5 and 10% β-AgVO 3 , there was better inhibition for the groups of 5 and 10% for Sealer, 2.5, 5 and 10% for Endomethasone, while AH-Plus presented similar results to the control group. In another study by Teixeira et al., 2019 [ 12 ] in which he added the same proportions to the same materials previously mentioned, there was complete inhibition of the growth of E. Faecalis, however, without significant differences between the groups, including control. In another study by Teixeira et al., 2017 [ 19 ], the incorporation of β-AgVO 3 did not increase the antimicrobial activity of AH Plus against E. Faecalis.…”
Section: Resultsmentioning
confidence: 89%
“…All groups showing an acidic pH in relation to the initial pH. Teixeira et al., 2019 [ 12 ]. Three endodontic sealers (AH Plus, Sealer 26 and Endomethasone N) 2.5%, 5% and 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the conversion of polymers from monomers occurs slowly [22]. The incorporation of chitosan nanoparticles into epoxy resin-based sealer produced a longer setting time compared to epoxy resin-based sealer because the addition of particles that do not contribute to the reaction during setting or polymerization may enhance the setting time [23].…”
Section: Discussionmentioning
confidence: 99%
“… 153 However, conflicting results have been published regarding its effects on the antibacterial activity of sealers. One study reported that there was no additional antibacterial benefit gained when the sealers were in a freshly mixed state, 154 whilst another reported enhanced antibacterial properties in both freshly mixed and set states. 155 Furthermore, the extent of benefit from the inclusion of silver vanadate nanowires decorated with AgNPs may depend on the type of commercial sealer and the concentration used.…”
Section: Obturation Materials and Root Canal Sealersmentioning
confidence: 99%